1999
DOI: 10.1016/s0022-3093(99)00048-4
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of the films of europium (III) with thenoyltrifluoroacetonate and macrocyclics

Abstract: We discuss the syntheses, properties and the luminescence of the complexes, Eu(TTA) 3 á 2L á H 2 O, where TTA thenoyltri¯uoroacetonate, L 15C5 (1,4,7,10-tetraoxa-13-azacyclopentadecane,13-phenyl) and 18C6 (2,3,11,12-dicyclohexano-1,4,7,10,13,16-hexaoxacyclooctadecane). The ®lm complexes with 15C5 and 18C6 ligands contain only one water molecule. The X k experimental intensity parameters (k 2 and 4) and the ratio between the intensities of the 5 D 0 ® 7 F 0 and 5 D 0 ® 7 F 2 transitions (R 02 ) were obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 16 publications
5
14
0
1
Order By: Relevance
“…This goes in the correct sense towards the rationalization of the so-called hypersensitive transitions, which are normally dominated by the effective operator Ω 2 U (2) . On the other hand, this also seems to agree with the empirical suggestion that the effects involving slight changes in the positions of the ligands belonging to the second coordination shell could be reflected in the Ω 4 U (4) and Ω 6 U (6) effective operators 29,30,31 . However, it has been observed that the symmetry alone cannot account for the enormous variation sometimes observed in the intensities of those hypersensitive transitions for different chemical environments.…”
Section: The Dynamic Couplingsupporting
confidence: 90%
“…This goes in the correct sense towards the rationalization of the so-called hypersensitive transitions, which are normally dominated by the effective operator Ω 2 U (2) . On the other hand, this also seems to agree with the empirical suggestion that the effects involving slight changes in the positions of the ligands belonging to the second coordination shell could be reflected in the Ω 4 U (4) and Ω 6 U (6) effective operators 29,30,31 . However, it has been observed that the symmetry alone cannot account for the enormous variation sometimes observed in the intensities of those hypersensitive transitions for different chemical environments.…”
Section: The Dynamic Couplingsupporting
confidence: 90%
“…In this work, Eu 3 + is introduced into a sodium cholate solution to generate functional photoluminescent hydrogels in a convenient way. As shown in the inset of Figure 1 a, the Eu 3 + -cholate system self-assembles into hybrid hydrogel at room temperature; the gel is a red-light emitter under UV light irradiation [11] , which is consistent with the single peak for…”
Section: Resultssupporting
confidence: 71%
“…This can be interpreted as the Eu 3 + ions occupying two types of chemical environments. [11] In this system, some Eu 3 + ions coordinate with cholate and are embedded inside the nanofibers; while others are in a free state without coordination to cholate. Upon further addition of sodium cholate, most of the Eu 3 + ions incorporate into nanofibers and consequently the split disappears.…”
Section: Supramolecular Nanostructures In Eumentioning
confidence: 99%
“…(2) , U (4) and U (6) reduced matrix elements, respectively, which allows the evaluation of intensity parameters Ω 2,4,6 directly from the emission spectra. The A i-j Einstein coefficient, the spontaneous emission probability of an electric dipole transition between 5 D i (i = 0) and 7 F j (j = 2, 4, 6), is given by [7] ( )…”
Section: Luminescence Of Eu Chelates Containing Pmmamentioning
confidence: 99%
“…The intensity of the [7]. This effect is mainly due to the mixing between the 7 F 2 manifold and the 7 F 0 level through the rank-two components of the crystal field, which is caused by the chemical environment around the rare-earth ions.…”
Section: Luminescence Of Eu Chelates Containing Pmmamentioning
confidence: 99%